Sliding mode controller optimization-based three-phase rectifier: review study - Mahmood, Omar Talal; Wan Hasan, Wan Zuha; Ismail, Luthffi Idzhar; Ramli, Hafiz Rashidi Harun (Institute of Electrical and Electronics Engineers (IEEE), 2024)
Numerous control strategies are used to optimize the performance of the three-phase rectifier. Sliding Mode Control (SMC) is chosen for its robustness, fast response, high-efficiency control, finite-time convergence, and other features. Several SMC methods utilized with three-phase rectifiers are outlined in this review study. This study is divided into two main parts; the first part discusses the technique used to optimize the performance of the rectifier, while the second part discusses the SMC algorithms used to enhance the performance of the rectifier. In addition to their theoretical components, this review paper investigates the practical implementation challenges of SMCs for three-phase rectifiers. This paper discusses the optimization parameters of SMC and stability and load fluctuation in the rectifier system. It introduces state-of-the-art algorithms that enhance the rectifier’s dynamic performance, including the adaptive and observation algorithms. This paper is vital for engineers, researchers, and experts focusing on the SMC of three-phase rectifiers. To our knowledge, no similar review of three-phase rectifiers is available for SMC. Finally, a research gap is identified – as far as we know, no predefined time (free-will arbitrary time) SMC algorithm is used to control the performance of any power electronic device, such as a three-phase rectifier. This active rectifier is used in our project to optimize the power system for the alternator used in our unmanned ground vehicle (UGV) as an oil palm autonomous grabber.